Peran Pola Asuh Keluarga terhadap Krisis Etika Anak dalam Interaksi Sosial - Nurul Safira Widianti; Haniah Hamidah; Lutfita Adelia Rahmah; Muhammad Luqman Baihaqi; Diska Aradea; Muhammad Farid Ilhamuddin (Universitas Palangka Raya, 2026)
This study aims to analyze the role of family parenting styles in children’s ethical crises in social interaction. This study employed a systematic literature review by examining relevant scholarly sources on family parenting styles, children’s ethics, moral development, and social interaction. The findings indicate that authoritarian parenting tends to shape externally driven obedience, which may limit children’s empathy, communication, and social decision-making. Permissive parenting contributes to weak self-control, low responsibility, and limited understanding of social norms. In contrast, democratic parenting shows the most positive tendency in fostering self-regulation, empathy, responsibility, and healthy social interaction. These findings suggest that the quality of family parenting plays an important role in shaping children’s social ethics. Therefore, the implementation of democratic parenting through open communication, clear boundaries, role modeling, and adequate emotional support is essential to prevent ethical crises in children’s social interaction.